ANALISIS IMPLEMENTASI SISTEM PENGUPAHAN BERDASARKAN UNDANG-UNDANG NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DI PT.ENLKA MITRA PERKASA - Indah Suci Pirani; Rachmat Gustiana; Doddy Mulyono; Guntur Syahputra Saragih (Gapenas Publisher, 2023)
The wage system is part of the protection of workers' rights which requires business institutions that have management and employ employees to pay wages. PT. Enlka Mitra Perkasa as a business institution that employs employees is included in the scope of business institutions that must provide wages in accordance with the provisions of Law Number 13 of 2003 concerning Manpower. Provisions in the Labor Law and its implementing regulations apply to employees of PT. Enlka Mighty Partners. In this study, the researcher proposed nyitepeeep nypynitiep